2021
DOI: 10.1021/acs.langmuir.1c02274
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molecular Competitive Adsorption Mechanism of CH4/CO2 in a Kerogen Matrix in the Presence of Moisture, Salinity, and Ethane

Abstract: Carbon dioxide (CO 2 ) injection in shale and coal seam gas reservoirs has become one of the most popular ways to promote methane (CH 4 ) production. However, geological factors affecting the CO 2 enhanced gas recovery (CO 2 -EGR) projects have not been studied in great depth, including underground moisture, subsurface water salinity, and other gases accompanying CH 4 . Thus, a hybrid methodology of molecular dynamics (MD) and grand canonical Monte Carlo (GCMC) simulation is employed to reveal the gas adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…These studies ignore the continuous pressure gradient in the direction of displacement and the back-pressure at the pore outlet. In addition, almost all current molecular simulation studies on CO 2 –CH 4 displacement use homogeneous organic or inorganic matter as pore surface materials. , In fact, heterogeneous surface pores composed of both organic and inorganic matter are abundant in the reservoir matrix and have a non-negligible influence on the competing adsorption behavior of gases within the pores. , Therefore, a molecular model that better fits the actual site conditions is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies ignore the continuous pressure gradient in the direction of displacement and the back-pressure at the pore outlet. In addition, almost all current molecular simulation studies on CO 2 –CH 4 displacement use homogeneous organic or inorganic matter as pore surface materials. , In fact, heterogeneous surface pores composed of both organic and inorganic matter are abundant in the reservoir matrix and have a non-negligible influence on the competing adsorption behavior of gases within the pores. , Therefore, a molecular model that better fits the actual site conditions is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found experimentally by the NMR technique that the process of CO 2 gas displacement of CH 4 can be divided into three stages: the initial stage of competitive adsorption, the dominant stage of competitive adsorption, and the attenuated stage of competitive adsorption . Most of the current studies have focused on the gas behavior during the dominant stage of competitive adsorption ,,, and the recovery, displacement efficiency, and gas separation at the attenuated stage of competitive adsorption. During the dominant phase of competitive adsorption, Zhang et al found that 0.65–0.7 nm pores exhibited the highest CO 2 selectivity. The pore size corresponding to the maximum methane recovery decreased with increasing pressure, and low temperature is in favor of methane recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Such a result, which deserves further investigation to fully understand the role of moisture content as a function of the kerogen type and maturity, suggests that the impact of moisture content is driven by the water/kerogen interactions but also the gas/water interactions and porosity of the kerogen sample. As an interesting extension of these works on the role of moisture content, Li et al 117 also considered the impact of water content and salinity on CO 2 injection in shale to foster methane recovery. Using a molecular model of type II-D kerogen, these authors considered the following thermodynamic conditions: 0−5 wt % moisture, 0−6 mol/L NaCl saline, and 0−5 wt % C 2 H 6 at different temperatures and pressures.…”
Section: Energymentioning
confidence: 99%
“…Several authors also considered the impact of moisture content on the coadsorption of gases, typically, CH 4 /CO 2 mixtures. , As illustrated in Figure , using four kerogen molecular models of different maturities, Huang et al investigated the adsorption of CH 4 , CO 2 , and their mixtures in kerogens as a function of moisture content. Upon increasing the moisture content, the CO 2 /CH 4 selectivity was found to increase for the two mature samples and the most immature sample but to decrease for one of the immature sample.…”
Section: Fluid Thermodynamics and Transport In Kerogenmentioning
confidence: 99%
“…In addition, CO 2 plays an essential role in agriculture, petroleum exploitation, and shale and coal seam gas extraction. 3 The separation of CO 2 /N 2 from flue gas has always been a hot topic in gas separation. Among various gas separation methods, pressure swing adsorption (PSA) is the most energy saving and cheapest technique.…”
Section: Introductionmentioning
confidence: 99%